MEANING OF POWER IN REGISTER MOBILE LEGENDS ONLINE GAME - Fadlilah, Afi; Batu, Yulius Lumban (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
Mobile Legends online game is one of the latest innovations by combining games as entertainment with increasingly sophisticated technology. The complex development of technology and the internet connected with human needs in general can present a breakthrough in online games . Players can be connected by the "chat column" or "feature voice chat " with the internet. The use of language in online games in general cannot be limited and happens without any restrictions on language situations between players. As a result, these words can dominate other players during the game in the Mobile Legends game. Register is present as a medium used to communicate between players in the Mobile Legends game. Halliday's theory in the realm of field/ situation , mode/ expectation , and tenor/ role will be used to present the meaning contained in the words of players Mobile Legends. To find out what the register presents meaning, Blummer's theory is used, known as symbolic interactionism/term meaning. The result is that almost all registers in the Mobile Legends online game have varied uses that are mastery of other players according to the context of the situation and conditions of the game